Discourses on Violence in Costa Rica, El Salvador, and Nicaragua: Social Perceptions in Everyday Life - Sebastian Huhn (German Institute of Global and Area Studies (GIGA), 2008)
Central America has the reputation of being a violent region with high crime rates, youth gangs, drug traffic, and ubiquitous insecurity. Politicians, the media, and social scientists in and outside the region often claim that the societies are in complete agreement with their judgment of the situation and that all society members are calling for law and order and social segregation. Focusing on Costa Rica, El Salvador, and Nicaragua, the paper analyzes the social perception of violence and crime. On the basis of essays written by secondary school students and interviews with citizens from all walks of life in the three countries, the paper points out how elite arguments on violence and crime are translated into everyday life, and what society members suggest be done to deal with these problems. The sources prove that there are noticeable hegemonic discourses on violence and crime in Costa Rica, El Salvador, and Nicaragua. Simultaneously, a majority of the respondents call for social and integrative solutions rather than the so-called 'iron fist'. The repressive trend in Central American policies therefore does not necessarily receive the presumed affirmation asserted by many authorities on and in the region. – – Zentralamerika steht in dem Ruf, eine sehr gewaltsame Region zu sein, in der hohe Verbrechensraten, brutale Jugendbanden, Drogenhandel und allgegenwärtige Unsicherheit den Alltag bestimmen. Politiker, die Medien sowie politische Beobachter in und außerhalb der Region behaupten oft, die Bevölkerung teile ihre Einschätzung der Situation unwidersprochen und plädiere für mehr law and order. Dieser Beitrag analysiert sowohl die gesellschaftliche Wahrnehmung von Gewalt und Kriminalität in Costa Rica, El Salvador und Nicaragua als auch die Vorstellungen zu möglichen Lösungen. Auf der Grundlage von Interviews und Schüleraufsätzen geht der Beitrag der Frage nach, welche Inhalte öffentlicher Aussagen bei der Bevölkerung Niederschlag finden. Die Quellen belegen, dass hegemoniale Diskurse über Gewalt, Kriminalität und Unsicherheit zirkulieren, die gültiges Wissen darstellen und Wirklichkeit konstruieren. Gleichzeitig scheint die Mehrheit der Bevölkerung den repressiven politischen Lösungsansätzen zu widersprechen.
Keywords: 300; Central America; violence; crime; public discourse; social perception